Functional dependence among older adults: a cross-sectional study with a rural population of southern Brazil - Rodrigo Meucci; Andrea Aguiar de Oliveira; Gabrielle Araújo; Tatiane Gonzalez; Giovanna Pagliaro; Tchurle Hoffmann; Luana Marmitt (James Cook University, 2020)
Introduction: Brazil has a rapidly aging population, yet little is known about the occurrence of functional dependence in the rural older adult population. The objective of this study was to estimate the prevalence of functional dependence and its associated factors among community-dwelling older adults in the rural area of the municipality of Rio Grande, Rio Grande do Sul state, Brazil. Methods: This was a cross-sectional, population-based study. A systematic random sampling of households was used. Eighty percent of households in the rural area were selected, which included 1131 older adults. The outcome analyzed in this study was functional dependence. This was measured by and data were collected using the Katz Index for Activities of Daily Living (ADL) and Lawton and Brody's Scale for Instrumental Activities of Daily Living (IADL). Descriptive analysis was used to estimate the prevalence of functional dependence in ADL and IADL and to describe the sample. Crude and adjusted analysis was performed by Poisson regression with robust adjustment of variance. Prevalence ratios (PRs) and 95% confidence intervals (95%CIs) were reported. Results: A total of 1029 older adults took part in this study, corresponding to an 8.9% rate of losses and refusals. Prevalence of functional dependence in ADL was 8.1% (95%CI 6.4-9.7), while prevalence of functional dependence in IADL was 32.4% (95%CI 29.5-35.2). The occurrence of functional dependence in one or more of ADL or IADL was 6.7% (95%CI 5.2-8.2). The following categories were associated with functional dependence in ADL: female sex (PR=1.70; 95%CI 1.10-2.62), age group 80 years or more (PR=3.68; 95%CI 2.20-6.16), no schooling (PR=2.61; 95%CI 1.26-5.37) and 1-4 years of schooling (PR=2.49; 95%CI 1.28-4.84), having diabetes (PR=1.85; 95%CI 1.21-2.83), depression in the previous year (PR=1.90; 95%CI 1.09-3.31), urinary incontinence (PR=3.26; 95%CI 2.06-5.16), history of stroke (PR=2.26; 95%CI 1.35-3.76) and poor/very poor self-rated health (PR=2.36; 95%CI 1.29-4.32). The following categories were associated with functional dependence in IADL: female sex (PR=1.40; 95%CI 1.19-1.65), age groups of 70-79 years (PR=1.92; 95%CI 1.51-2.43) and 80 years or more (PR=3.80; 95%CI 3.07-4.72), no schooling (PR=1.87; 95%CI 1.46-2.41) and 1-4 years of schooling (PR=1.55; 95%CI 1.22-1.96), medical diagnosis of diabetes (PR=1.33; 95%CI 1.10-1.60), urinary incontinence (PR=1.40; 95%CI 1.17-1.68), history of stroke (PR=1.41; 95%CI 1.10-1.81) and regular self-rated health (PR=1.27; 95%CI 1.06-1.52) or poor/very poor self-rated health (PR=1.80; 95%CI 1.41-2.30). Conclusion: Older adults in rural areas have a high prevalence of functional dependence. Knowledge of functional dependence and associated factors in rural populations is necessary for the planning and developing actions, especially in the routine of primary care, which promote health and prevent or postpone the decline in functional capacity.